2016
DOI: 10.18203/2349-3291.ijcp20164605
|View full text |Cite
|
Sign up to set email alerts
|

A study on the awareness of the weaning practices and the determinants affecting them in a rural hospital based pediatric outpatient clinic of Maval Taluka, Maharashtra

Abstract: Background: Malnutrition and micronutrient deficiencies is a very common cause of late weaning and improper weaning practices. There are many factors affecting the weaning practices in developing countries like India which may act as hindrance to the proper weaning methods. The objective of this study was to know the awareness about weaning or complementary feeding practices in the mothers of children attending the pediatric OPD. And to study the various determinants affecting the weaning or Complementary feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…The study is noteworthy for a greater number of participants enrolled than in several other institution-based studies [18][19][20][21]. Although community-based surveys are considered more representative, the importance of institution-based studies cannot be undermined, as they help in identification of priorities requiring action and also provide clues for the required interventions.…”
Section: Complementary Feeding In Childrenmentioning
confidence: 99%
“…The study is noteworthy for a greater number of participants enrolled than in several other institution-based studies [18][19][20][21]. Although community-based surveys are considered more representative, the importance of institution-based studies cannot be undermined, as they help in identification of priorities requiring action and also provide clues for the required interventions.…”
Section: Complementary Feeding In Childrenmentioning
confidence: 99%
“…Any thick porridge like, liquid or mashed food with nutritional energy, that a child receives in addition to breast milk is called weaning. Such foods are particularly made ready for infants before they shift to adult diet therefore it is also known as transition foods which initiate the weaning process 2 . An appropriate diet plays an essential role in the proper nourishment.…”
Section: Introductionmentioning
confidence: 99%
“…This process involves nutritional, immunological, biochemical, microbiologic and psychological adjustments in both the mother and child (Lawrence & Lawrence, 2016). Incorrect weaning practices are major contributory factors for increasing malnutrition and stunted growth (Ambike, Bhavari, Poker, & Ahmed, 2017;Shamim, Naz, Jamalvi, & Ali, 2006). A study conducted by Vyas, Kandpal, Semwal, Chauhan, and Nautiyal (2014) revealed that inappropriate weaning practices not only lead to malnutrition but also contribute to poor cognitive and learning abilities, and poor performance later in life.…”
Section: Introductionmentioning
confidence: 99%